Heat penetration patterns of outside round, loin strip and eye round muscles cooked by electric broiler, electric belt grill, or forced-air convection oven - Obuz, E.; Yancey, E.J.; Lawrence, T.E.; King, D.A.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used an electric belt grill, a forced air convection oven, and an electric broiler to cook steaks from three beef muscles; outside round (biceps femoris), loin strip (longissimus lumborum) and eye round (semitendinosus). Belt grill cookery gave the fastest heat penetration into steaks regardless of temperature interval. Eye round had the slowest heat transfer rate for each cooking method perhaps partially explained by its fiber orientation. Heat penetration rate into outside round and loin strip was not different (P>0.05) for cooking method within a given temperature range. Heat penetration into muscles between 140 and 158°F was slowest because energy-expensive reactions (collagen and protein denaturation) occur in that temperature and temperature differential between the heat source and meat is less. Heat penetration also was slow between 122 and 140°F due to the denaturation of contractile proteins.
Keywords: Beef; Heat penetration; Belt grill; Forced-air convection oven; Electric broiler